COMMUNITY PARTICIPATION IN WASTE MANAGEMENT AS A MEDIATION OF THE EFFECT OF REALIGY UNDERSTANDING ON ENVIRONMENTAL CLEANLINESS IN YOUR DISTRICT, DOGIYAI REGENCY, PAPUA - Ella Adelin Hurulean; Sugiyanto (International Journal of Social Science, 2022)
The research entitled Community Participation in Waste Management as Mediating Realistic Understanding of Environmental Hygiene in the Community of Kamu Subdistrict, Dogiyai Regency, Papua aims to determine: 1) religious understanding affects environmental cleanliness 2) community participation affects environmental cleanliness 3) community participation mediates the influence of understanding religion to environmental cleanliness. The population in this study was the entire community of Dogiyai District, Kamu District, Dogiyai Regency. The sampling technique used was purposive sampling. The data was obtained by distributing questionnaires to 44 respondents from the Kamu sub-district, Dogiyai district. The data analysis technique in this study is Partial Least Square using the WarpPLS 7.0 application. The results showed that 1) religious understanding had an effect on environmental cleanliness 2) community participation had an effect on environmental hygiene 3) community participation mediated some of the influence of religious understanding on environmental cleanliness